Differential regulation of cellular stress responses by the endoplasmic reticulum‐resident Selenoprotein S (Seps1) in proliferating myoblasts versus myotubes. Issue 24 (17th December 2018) - Addinsall, Alex B.; Martin, Sheree D.; Collier, Fiona; Conlan, Xavier A.; Foletta, Victoria C.; Stupka, Nicole
Abstract: The antioxidant Selenoprotein S (Seps1, Selenos ) is an endoplasmic reticulum (ER)‐resident protein associated with metabolic and inflammatory disease. While Seps1 is highly expressed in skeletal muscle, its mechanistic role as an antioxidant in skeletal muscle cells is not well characterized. In C2C12 myotubes treated with palmitate for 24 h, endogenous Seps1 protein expression was upregulated twofold. Two different siRNA constructs were used to investigate whether decreased levels of Seps1 exacerbated lipid‐induced oxidative and ER stress in C2C12 myotubes and myoblasts, which differ with regards to cell cycle state and metabolic phenotype. In myoblasts, Seps1 protein knockdown of ~50% or ~75% exacerbated cellular stress responses in the presence of palmitate; as indicated by decreased cell viability and proliferation, higher H2 O2 levels, a lower reduced to oxidized glutathione (GSH:GSSG) ratio, and enhanced gene expression of ER and oxidative stress markers. Even in the absence of palmitate, Seps1 knockdown increased oxidative stress in myoblasts. Whereas, in myotubes in the presence of palmitate, a ~50% knockdown of Seps1 was associated with a trend toward a marginal (3‐5%) decrease in viability ( P  =   0.05), decreased cellular ROS levels, and a reduced mRNA transcript abundance of the cellular stress marker thioredoxin inhibitory binding protein ( Txnip ). Furthermore, no enhancement of gene markers of ER stress was observed in palmitate‐treated myotubes in response to Seps1 knockdown. In conclusion, reduced Seps1 levels exacerbate nutrient‐induced cellular stress responses to a greater extent in glycolytic, proliferating myoblasts than in oxidative, differentiated myotubes, thus demonstrating the importance of cell phenotype to Seps1 function. Abstract : Selenoprotein S (Seps1), an ER‐resident antioxidant protein, is responsive to nutrient stress and is highly expressed in skeletal muscle. Here, proliferating, glycolytic C2C12 myoblasts or differentiated, oxidative C2C12 myotubes were treated with palmitate following Seps1 gene knockdown. We report that cell cycle state and metabolic phenotype differentially influence the regulation of cellular stress responses by Seps1.